Clinical symptoms of COVID-19 pneumonia in children: A protocol for systematic review and meta-analysis. Issue 1 (8th January 2021) - Tang, Zhengwu; Li, Muzhe; Chen, Wei; Ran, Xun; Li, Huiyun; Chen, Zhiwei
Abstract: Background: This meta-analysis aimed to compare the clinical symptoms of COVID-19 pneumonia in children. Methods and analysis: Electronic databases including PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI) database, Wanfang Database, and Chinese Biomedical Literature Database (CBM) were searched from its inception to June 21, 2020. We only included studies that reported clinical symptoms of COVID pneumonia in children. Quality of the included studies was assessed by 2 authors. Pooled results were summarized by STATA 12.0 software. The heterogeneity was measured by I 2 tests ( I 2  < 50 indicates little heterogeneity, I 2 ≥50 indicates high heterogeneity). Publication bias was performed by funnel plot and statistically assessed by Begg test ( P  > .05 as no publication bias). Results: Results will be shown as figures or tables. Conclusion: Our study aims to systematically present the clinical symptoms of COVID-19 pneumonia patients in children, so as to further provide guidance for clinical management.